Pembagian Hadist dari Segi Jumlah Perawinya - Madsuri (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2022)
The main basis of Islamic teachings after the Qur'an is the As-Sunnah (Al-Hadith). When studying Hadith. You will find many problems because besides there are three main things, namely: sanad, matan, and rawi. In the hadith there are still some problems that need special study. This is where questions will arise, what is sanad? What is Matan? What is Rawi? How is the journey of the hadith scholar? whether prominent hadith figures and so on. Being a kaffah Muslim woman is far from heresy and not blind is our dream. Therefore, to make it happen we need to meet the main requirements, one of which is to study the hadith and its knowledge in detail is an obligation.